Hypoxia-Induced Aquaporins and Regulation of Redox Homeostasis by a Trans-Plasma Membrane Electron Transport System in Maize Roots - Anne Hofmann; Stefanie Wienkoop; Sabine Lüthje (MDPI AG, 2022)
In plants, flooding-induced oxygen deficiency causes severe stress, leading to growth reduction and yield loss. It is therefore important to understand the molecular mechanisms for adaptation to hypoxia. Aquaporins at the plasma membrane play a crucial role in water uptake. However, their role during hypoxia and membrane redox changes is still not fully understood. The influence of 24 h hypoxia induction on hydroponically grown maize (Zea mays L.) was investigated using an oil-based setup. Analyses of physiological parameters revealed typical flooding symptoms such as increased ethylene and H2O2 levels, an increased alcohol dehydrogenase activity, and an increased redox activity at the plasma membrane along with decreased oxygen of the medium. Transcriptomic analysis and shotgun proteomics of plasma membranes and soluble fractions were performed to determine alterations in maize roots. RNA-sequencing data confirmed the upregulation of genes involved in anaerobic metabolism, biosynthesis of the phytohormone ethylene, and its receptors. Transcripts of several antioxidative systems and other oxidoreductases were regulated. Mass spectrometry analysis of the plasma membrane proteome revealed alterations in redox systems and an increased abundance of aquaporins. Here, we discuss the importance of plasma membrane aquaporins and redox systems in hypoxia stress response, including the regulation of plant growth and redox homeostasis.